Ecotourism and Natural Resources in Dominica: Co-management as an Innovative Practice - Sarrasin, Bruno; Tardif, Jonathan (Téoros)

(untitled) (Université du Québec à Montréal, 2012)
Tourism is one of the major outcomes of globalization, which also brings new challenges to local authorities. In this perspective, co-management could be analyzed as an innovative practice in promoting natural resources-oriented tourism. Moreover, it raises the following question: how does power sharing – on which co-management is based – contribute to local development? This question could be answered through a case study using political ecology which could contribute to renew the reading of ecotourism through an innovative analytical framework.